A panel VAR analysis of macro-financial imbalances in the EU - Mariarosaria Comunale (European Central Bank (ECB), 2017)
We investigate the interactions across current account misalignments, Real Effective Exchange Rate misalignments and financial (or output) gaps within EU countries. We apply panel techniques, including a Bayesian panel VAR, to 27 EU members over the period 1994-2012. We find that, for the euro area, the reaction of current account misalignments to a shock in the Real Effective Exchange Rate misalignments is the largest and the financial gap can influence the current account misalignments more than the output gap. In non-euro area countries and euro periphery an increase in current account misalignments leads to a temporary increase in the Real Effective Exchange Rate misalignments, lowering competitiveness and thus amplifying current account fluctuations. For the core, a raise in the rate or an expansion of the financial gap may help in rebalancing the current account. In the CEE members, an increase in the Real Effective Exchange Rate misalignments may bring larger current account deficits in the medium-long run.
Keywords: F32; F31; C33; 330; current account; real effective exchange rate; financial gaps; panel VAR; foreign capital flows